2017
DOI: 10.3126/ijasbt.v4i4.16269
|View full text |Cite
|
Sign up to set email alerts
|

Study on Genotypic Response and Correlation Analysis of the Yield and Yield Attributing Traits of Different Barley (Hordeum Vulgare) Genotypes

Abstract: Barley, being a tremendous opportunities crop, we are far back regarding study, research and utilization. An experiment was conducted 2014-2015 to evaluate the barley genotypes for their yield attributing traits and correlation and causation. Eleven yield contributing traits viz., days to booting, heading and flowering; peduncle length, spike length, plant height, flag leaf area, flag leaf-1 area, thousand grain weight, biological weight and yield per hectare were recorded. High significant variation among gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…In the article published by (Vitrakoti et al, 2016),grain yield in keeping with hectare had advantageous and noticeably massive end resultwith thousand seed weight (which was positive but non-significant in our result), positive and significant correlation with spike length (which was negative and non-significant in our result) whereas grain yield per hectare showed negative highly significant correlation with days to flowering. Although there exists positive relationship between yield and the other components, the negative correlation between some of them cannot make a useful choice for all as a factor in increasing the yield (Kannenberg 1976).There was nonsignificant positive correlation between plant height and thousand seed weight (Drikvand 2011), which was positive and highly significant in our result.…”
Section: Yield and Yield Attributing Traitscontrasting
confidence: 49%
See 2 more Smart Citations
“…In the article published by (Vitrakoti et al, 2016),grain yield in keeping with hectare had advantageous and noticeably massive end resultwith thousand seed weight (which was positive but non-significant in our result), positive and significant correlation with spike length (which was negative and non-significant in our result) whereas grain yield per hectare showed negative highly significant correlation with days to flowering. Although there exists positive relationship between yield and the other components, the negative correlation between some of them cannot make a useful choice for all as a factor in increasing the yield (Kannenberg 1976).There was nonsignificant positive correlation between plant height and thousand seed weight (Drikvand 2011), which was positive and highly significant in our result.…”
Section: Yield and Yield Attributing Traitscontrasting
confidence: 49%
“…Highly significant favorable correlation among yield attributing tendencies suggests that, the unit increment in one of the trait will motive a unit increment inside the every other relatedtraits, which in turn will lead to increase in the grain yield. Hence, these traits could be pointed and noted for the improvement of grain yield by focusing on the associated traits (Vitrakoti 2016).…”
Section: Yield and Yield Attributing Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of stress depended on the time, duration and intensity. Although it has been higher under irrigated condition, plant height of barley showed low positive correlation with yield [9]. Okuyama et al [10] reported that under non-irrigated condition, yield has a positive moderate correlation with culm diameter and plant height.…”
Section: Drought Stress On the Agromorphology Of Barleymentioning
confidence: 97%